Towards the creation of a cultural community of Spanish-speaking countries - Vargas G, Lola (Revista de Psicología, 1992)
As the title indicates, it is an approach to the idea of "creating a community", of a common language, in this case, Spanish. Establishing the bases so that -if this need materializes- there is a reopening of man in relation to what, in truth, is a community. And, for this very reason, it stops at an analysis of "language" and "respect" as undeniable bases in the existence of a "community".